Motivated Down-Regulation of Emotion and Compassion Collapse Revisited - Hagman, William; Tinghög, Gustav; Dickert, Stephan; Slovic, Paul; Västfjäll, Daniel (Frontiers in Psychology, 2022)
Compassion collapse is a phenomenon where feelings and helping behavior decreases as the number of needy increases. But what are the underlying mechanisms for compassion collapse? Previous research has attempted to pit two explanations, limitations of the feeling system vs motivated down regulation of emotion, against each other (Cameron & Payne, 2011). In this article we critically re-examine the study by Cameron and Payne (2011) and present new data that contest motivated down regulation of emotion as the primary explantion for compassion collapse.